Early changes in cerebral autoregulation among youth hospitalized after sports-related traumatic brain injury. (28th January 2018) - Vavilala, Monica S; Farr, Carly K; Watanitanon, Arraya; Clark-Bell, BS Crystalyn; Chandee, Theerada; Moore, Anne; Armstead, William
ABSTRACT: Objective : To examine early cerebral haemodynamic changes among youth hospitalized with sports-related traumatic brain injury (TBI). Study design : Youth 0–18 years admitted to a level one trauma centre with sports-related TBI were enrolled. Daily measures included clinical symptoms and Glasgow Coma Scale (GCS) score. Using Transcranial Doppler (TCD) ultrasonography and tilt testing, we measured middle cerebral artery flow velocity (Vmca) and cerebral autoregulation index (ARI). Results : Six previously healthy males age 14 (IQR 12–16) years with headache and abnormal head CT were admitted with median admission GCS 15. Six patients underwent 12 TCD examinations between hospital days 0–9. Low Vmca occurred in 3/6 patients and on the side of TBI, whereas high Vmca occurred in 2/6 patients. Five patients had at least one measurement of impaired and five patients had absent cerebral autoregulation of at least one hemisphere; all these five patients had GCS 15 and headache during TCD examinations. Three patients were discharged with absent cerebral autoregulation. Five (83%) patients were discharged to home and one patient was discharged to a rehabilitation facility. Conclusion : Headache, abnormal Vmca and impaired cerebral autoregulation occur after sports-related TBI, despite normal GCS. Headache may signal underlying neurovascular abnormality in sports-related TBI.